Experimental cryptorchidism enhances testicular susceptibility to dibutyl phthalate or acrylamide in Sprague-Dawley rats - de Souza, N. P. [UNESP] (2019)
Cryptorchidism (CPT), the most common male congenital abnormality, is variably associated with other male reproductive tract problems. We evaluated if cryptorchid rats develop enhanced testicular susceptibility to dibutyl phthalate (DBP) or acrylamide (AA) after extended exposure. Three studies with rats were performed: (1) in utero and postnatal exposure to DBP or AA; (2) establishment of CPT and orchiopexy; and (3) in utero and postnatal exposures to DBP or AA associated with CPT/orchiopexy. Seminiferous tubules were histologically scored according to the severity of lesions: (1) Rats exposed to DBP (score 1.5) or AA (score 1.1) presented mostly preserved spermatogenesis. Some seminiferous tubules showed vacuolated germinative epithelium, germ cell apoptosis, and a Sertoli cell-only (SCO) pattern. (2) CPT (score 3.3) resulted in decreased absolute testes weights, degenerated and SCO tubules, and spermatogenesis arrest that were reversed by orchiopexy (score 1.1). (3) Exposure to DBP or AA with CPT/orchiopexy led to atrophic testes, spermatogenesis arrest, germ cell exfoliation/multinucleation, and SCO tubules (both chemicals score 2.5). Exposure to chemicals such as DBP or AA prevented the recovery of cryptorchid testes by orchiopexy. The possible role of environmental contaminants should be considered when looking for factors that modulate human testicular disorders associated with CPT.